uc.454 Inhibited Growth by Targeting Heat Shock Protein Family A Member 12B in Non-Small-Cell Lung Cancer - Jun Zhou; Chenghai Wang; Weijuan Gong; Yandan Wu; Huimin Xue; Zewei Jiang; Minhua Shi (Elsevier, 2018)
Transcribed ultraconserved regions (T-UCRs) classified as long non-coding RNAs (Lnc-RNAs) are transcripts longer than 200-nt RNA with no protein-coding capacity. Previous studies showed that T-UCRs serve as novel oncogenes, or tumor suppressors are involved in tumorigenesis and cancer progressive. Nevertheless, the clinicopathologic significance and regulatory mechanism of T-UCRs in lung cancer (LC) remain largely unknown. We found that uc.454 was downregulated in both non-small-cell LC (NSCLC) tissues and LC cell lines, and the downregulated uc.454 is associated with tumor size and tumors with more advanced stages. Transfection with uc.454 markedly induced apoptosis and inhibited cell proliferation in SPC-A-1 and NCI-H2170 LC cell lines. Above results suggested that uc.454 played a suppressive role in LC. Heat shock protein family A member 12B (HSPA12B) protein was negatively regulated by uc.454 at the posttranscriptional level by dual-luciferase reporter assay and affected the expressions of Bcl-2 family members, which finally induced LC apoptosis. The uc.454/HSPA12B axis furthers our understanding of the molecular mechanisms involved in tumor apoptosis, which may potentially serve as a therapeutic target for lung carcinoma. Keywords: uc.454, HSPA12B, NSCLC, lung cancer, apoptosis, proliferation